Disease patterns and causes of death of hospitalized HIV‐positive adults in West Africa: a multicountry survey in the antiretroviral treatment era. Issue 2 (7th April 2014) - Lewden, Charlotte; Drabo, Youssoufou J; Zannou, Djimon M; Maiga, Moussa Y; Minta, Daouda K; Sow, Papa S; Akakpo, Jocelyn; Dabis, François; Eholié, Serge P; ,
Abstract : Objective: We aimed to describe the morbidity and mortality patterns in HIV‐positive adults hospitalized in West Africa. Method: We conducted a six‐month prospective multicentre survey within the IeDEA West Africa collaboration in six adult medical wards of teaching hospitals in Abidjan, Ouagadougou, Cotonou, Dakar and Bamako. From April to October 2010, all newly hospitalized HIV‐positive patients were eligible. Baseline and follow‐up information until hospital discharge was recorded using standardized forms. Diagnoses were reviewed by a local event validation committee using reference definitions. Factors associated with in‐hospital mortality were studied with a logistic regression model. Results: Among 823 hospitalized HIV‐positive adults (median age 40 years, 58% women), 24% discovered their HIV infection during the hospitalization, median CD4 count was 75/mm 3 (IQR: 25–177) and 48% had previously received antiretroviral treatment (ART). The underlying causes of hospitalization were AIDS‐defining conditions (54%), other infections (32%), other diseases (8%) and non‐specific illness (6%). The most frequent diseases diagnosed were: tuberculosis (29%), pneumonia (15%), malaria (10%) and cerebral toxoplasmosis (10%). Overall, 315 (38%) patients died during hospitalization and the underlying cause of death was AIDS (63%), non‐AIDS‐defining infections (26%), other diseases (7%) and non‐specific illness or unknown cause (4%). Among them, the most frequent fatal diseases were: tuberculosis (36%), cerebral toxoplasmosis (10%), cryptococcosis (9%) and sepsis (7%). Older age, clinical WHO stage 3 and 4, low CD4 count, and AIDS‐defining infectious diagnoses were associated with hospital fatality. Conclusions: AIDS‐defining conditions, primarily tuberculosis, and bacterial infections were the most frequent causes of hospitalization in HIV‐positive adults in West Africa and resulted in high in‐hospital fatality. Sustained efforts are needed to integrate care of these disease conditions and optimize earlier diagnosis of HIV infection and initiation of ART.